An evaluation of the counselling and appraisal services in Colleges of Education in the Volta region of Ghana - Sedofia, John; Ocansey, Frederick (Journal of Educational Development and Practice, 2013)
The main objective of this study was to evaluate the counselling and appraisal services in the Colleges of Education in the Volta Region of Ghana. The research design used for the study was the survey approach. Four hundred research participants made up of 317 students, 80 tutors and three counsellors were selected from three Colleges of Education in the Volta Region through stratified and purposive sampling procedures. Stratified sampling technique was used to select the students and tutors while the counsellors were selected purposively. Data were collected with questionnaire and analysed using frequencies and percentages. The results revealed that teacher trainees were not benefiting fully from both the counselling and appraisal services. Some of the recommendations made were that counsellors should intensify guidance activities in the colleges so as to make guidance services, especially the counselling and appraisal services more attractive and accessible to students. In addition, college authorities should play a supervisory role to ensure that counsellors organise guidance activities in the key service areas on periodic bases, just like other co-curricular activities such as sports.